The Launch of Ethiopia’s Climate-Smart Agriculture Investment Plan: From Strategy to Implementation - Jalango, Dorcas; Tesfaye, Lidya; Yemane, Melat; Makonnen, Brook T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Key messages - Align climate actions with strategic investments and private-sector engagement for widespread impact - Strengthen Ethiopia’s Climate-Smart Agriculture (CSA) Forum through broader membership, coordination and policy alignment - Tailor investments in the CSAIP to ensure benefits reach farmers and communities